Albuca Bracteata Polysaccharides Attenuate AOM/DSS Induced Colon Tumorigenesis via Regulating Oxidative Stress, Inflammation and Gut Microbiota in Mice - Qin, Ziyan; Yuan, Xinyu; Liu, Jian; Shi, Zhuqing; Cao, Leipeng; Yang, Lexuan; Wu, Kai; Lou, Yongliang; Tong, Haibin; Jiang, Lei; Du, Jimei (Frontiers in Pharmacology, 2022)
Inflammation is an important risk factor in the development of inflammatory bowel disease (IBD) and colitis-associated colorectal cancer (CAC). Accumulating evidence indicates that some phytochemicals have anti-cancer properties. Polysaccharides extracted from Albuca bracteata (AB) have been reported to possess anti-neoplastic activities on xenograft colorectal cancer (CRC) models. However, it is still unclear whether they exert therapeutic effects on CAC. In this study, we investigate the properties of polysaccharides of A. bracteate, named ABP. The average molecular weight of ABP was 18.3 kDa and ABP consisted of glucose, mannose, galactose, xylose, galacturonic acid, glucuronic acid at a molar ratio of 37.8:8:2.5:1.7:1:1. An Azoxymethane/Dextran sodium sulfate (AOM/DSS) induced CAC mouse model was established. The CAC mice treated with ABP showed smaller tumor size and lower tumor incidence than untreated ones. ABP increased anti-inflammatory cytokine IL-10, inhibited secretion of pro-inflammatory cytokines (IL-6, IFN-γ, and TNF-α), mitigated oxidative stress by increasing GSH and decreasing MDA levels, suppressed the activation of STAT3 and expressions of its related genes c-Myc and cyclin D1. Moreover, ABP treatment increased the relative abundance of beneficial bacteria (f_Ruminococcaceae, g_Roseburia, g_Odoribacter, g_Oscillospira, and g_Akkermansia) and the levels of fecal short-chain fatty acid (SCFA) in CAC model mice. In summary, our data suggest that ABP could be a potential therapeutic agent for treating CAC.